Electropolymerisation of pyrrole onto aluminium from alkaline solutions containing a surfactant - Saidman, Silvana Beatriz (2005)
Polypyrrole films have been successfully electrodeposited on aluminium substrates from alkaline solutions containing an anionic surfactant (sodium dodecyl sulphate or sodium dodecylbenzene sulfonate). Homogeneous and adherent films were formed under potentiostatic, galvanostatic and potentiodynamic control. The electrochemical response was compared to that obtained with vitreous carbon as a substrate. Studies performed in monomer-free solutions showed that both OH- and Na+ play an important role in the redox process. Scanning electron microscopy and atomic force microscopy studies indicated that the presence of surfactants influences the morphology of the polymer producing more homogeneous and less rough films than those formed in absence of surfactants.